Network protocols - Naugle, Matthew G (McGraw-Hill series on computer communications., 1999)
This handbook is a reference to the plethora of protocols that govern cyberspace. The text includes facts on protocols such as Gigabit Ethernet, IPv6, RSVP, and RTSP, as well as Ethernet, Token Ring, Novell NetWare, TCP/IP, and AppleTalk.